1994
DOI: 10.1002/hec.4730030304
|View full text |Cite
|
Sign up to set email alerts
|

Private versus social opportunity cost of time: Valuing time in the demand for health care

Abstract: In this paper we examine whether the current method of valuing time within economic appraisals is appropriate. The cost to society of time taken to use health care may differ from the private opportunity cost of such time. However, demand for health care may be affected by the private opportunity time cost and not by the value of time to society. In this paper we show that the private opportunity cost of time is a better predictor of demand for a screening service than the societal approach. It is important, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 10 publications
1
29
0
1
Order By: Relevance
“…This hypothesis rests on the assumption that people seek to minimize travel time to the physician. This is consistent with past studies that have shown that travel time is an important cost in the demand for medical care [10][11][12][13].…”
Section: Internal Validitysupporting
confidence: 93%
See 1 more Smart Citation
“…This hypothesis rests on the assumption that people seek to minimize travel time to the physician. This is consistent with past studies that have shown that travel time is an important cost in the demand for medical care [10][11][12][13].…”
Section: Internal Validitysupporting
confidence: 93%
“…While directly asking people about travel time might be novel, using an individual's actual travel time as a determinant of medical care utilization has a longer tradition [10][11][12][13]17]. Recently, Clarke, [18] used travel costs, which include time, as part of a cost-benefit model for mobile mammography screening units.…”
Section: Discussionmentioning
confidence: 99%
“…Time lost from paid labour was valued in our study using the human capital approach. 29,30 This approach applies current average earnings to lost time by age and gender. To value time lost from the labour market, age/sex based earnings estimates from the 2001 Census were adjusted for 15% nominal earnings growth to 2007, A multiplied by 1.20 for employer paid benefits, 31 and further multiplied by 52/46 to account for vacation days and holidays.…”
Section: Discussionmentioning
confidence: 99%
“…A total out-of-pocket cost was calculated for each participant by summing the amounts reported and then subtracting any reimbursements received from drug plans or insurance. Time costs were determined by assigning a monetary value to each unit of time, using the human capital approach (Rice and MacKenzie 1989;Torgerston et al 1994). The human capital approach applies current average earnings by age and gender to lost time.…”
Section: Discussionmentioning
confidence: 99%